2019
DOI: 10.3233/jad-180982
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Hyperintensities in Alzheimer’s Disease: A Lesion Probability Mapping Study

Abstract: Background/Objective: Higher white matter hyperintensity (WMH) load has been reported in Alzheimer's disease (AD) patients in different brain regions when compared to controls. We aimed to assess possible differences of WMH spatial distribution between AD patients and age-matched controls by means of lesion probability maps. Methods: The present study included MRI scans of 130 probable AD patients with a mean age of 73.4 ± 8.2 years from the Prospective Dementia Registry Austria Study and 130 age-matched healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…White matter hyperintensities (WMH) are commonly seen in brain MRI in older people and beside their underlying heterogeneous histopathology, they represent radiological correlates of cognitive and functional impairment (Prins and Scheltens, 2015). In a previous study, we found WMHs preferentially in a bilateral periventricular location, partly overlapping with the regions identified here by the Graz + -based models (Damulina et al, 2019). Furthermore, other plausible contributors are increased brain iron deposition in the deep gray matter (basal ganglia) of AD patients (Damulina et al, 2020) or cumulative gadolinium deposition of macrocyclic contrast agents (Kanda et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…White matter hyperintensities (WMH) are commonly seen in brain MRI in older people and beside their underlying heterogeneous histopathology, they represent radiological correlates of cognitive and functional impairment (Prins and Scheltens, 2015). In a previous study, we found WMHs preferentially in a bilateral periventricular location, partly overlapping with the regions identified here by the Graz + -based models (Damulina et al, 2019). Furthermore, other plausible contributors are increased brain iron deposition in the deep gray matter (basal ganglia) of AD patients (Damulina et al, 2020) or cumulative gadolinium deposition of macrocyclic contrast agents (Kanda et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…1. From the initial search, 162 articles were retrieved with 38 of them being analyzed 19,21–57 . All included studies were prospective; five had an intraindividual study design with two 21,24,31,40 or three study groups 19 that were examined separately.…”
Section: Resultsmentioning
confidence: 99%
“…They are associated with vascular risk factors (VRF), for example, hypertension or diabetes, 1 and with worse cognitive performance, particularly executive functions and processing speed. [2][3][4] In patients with Alzheimer's disease (AD), WMH volume appears to be larger than in cognitively unimpaired older adults, 5 particularly in periventricular [6][7][8] and posterior regions. These include parietooccipital regions 9,10 and the splenium of the corpus callosum (S-CC).…”
Section: Introductionmentioning
confidence: 99%